2007
DOI: 10.1136/ard.2007.077263
|View full text |Cite
|
Sign up to set email alerts
|

Selective p38MAPK isoform expression and activation in antineutrophil cytoplasmatic antibody-associated crescentic glomerulonephritis: role of p38MAPK 

Abstract: This study shows selective p38MAPK isoform expression and activation in crGN. Podocytes and podocyte-induce crescent formation is the main source of p38MAPK activation in crGN. TNF is a potent and selective activator of the alpha-isoform in podocytes, which therefore appears as a main contributor to proinflammatory signalling in the glomerulum of crGN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…This approach was based on the fact that abnormally activated p38 MAPK signaling in podocytes was observed in human disease, as well as in several animal models of NS (11,31,46,52,(57)(58)(59)68). By protecting PAN-injured cultured podocytes with the p38 MAPK inhibitor SB203580, we were able to confirm this concept.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This approach was based on the fact that abnormally activated p38 MAPK signaling in podocytes was observed in human disease, as well as in several animal models of NS (11,31,46,52,(57)(58)(59)68). By protecting PAN-injured cultured podocytes with the p38 MAPK inhibitor SB203580, we were able to confirm this concept.…”
Section: Discussionsupporting
confidence: 57%
“…In human crescentic glomerulonephritis, as well as experimental animal models of glomerulonephritis, activated p38 MAPK signaling has been observed in podocytes (46,52,(57)(58)(59). Similarly, increased phosphorylation (activation) of p38 MAPK has been reported in various human glomerulopathies as well as in experimental rodent nephrosis models (31).…”
mentioning
confidence: 99%
“…The p38a and p38b isoforms play predominant roles in immune cell activation, so the majority of p38 MAPK inhibitors developed for the treatment of inflammation have been targeted against these isoforms in order to avoid unwanted physiological effects through p38c and p38d inhibition. It has been shown in glomerulonephritis that p38a is the most highly expressed isoform in infiltrating leukocytes in the kidney [17], but there was also evidence of p38b and p38c isoform expression in structural cell types. The expression levels of p38 MAPK isoforms in the lungs of COPD patients have not been quantitatively studied; this would identify the isoforms relevant to the pathophysiology of COPD.…”
Section: Introductionmentioning
confidence: 98%
“…A further study demonstrated that both podocytes and the crescent lesion are the main source of p38MAPK activation, although additional signaling pathways could not be excluded. 18 Recent studies suggest that the mammalian target of rapamycin complex 1 (mTORC1) cascade has a regulatory …”
mentioning
confidence: 99%
“…A further study demonstrated that both podocytes and the crescent lesion are the main source of p38MAPK activation, although additional signaling pathways could not be excluded. 18 Recent studies suggest that the mammalian target of rapamycin complex 1 (mTORC1) cascade has a regulatory role in the signaling pathways that control cellular growth and proliferation. 19,20 Signaling through the mTORC1 pathway is activated by growth factors and nutrients, of which branched-chain amino acids (BCAA) are potent intracellular stimulators.…”
mentioning
confidence: 99%